2022
DOI: 10.1186/s41256-022-00278-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining membership in community-based health insurance in West Africa: a scoping review

Abstract: Background In many low-income countries, households bear most of the health care costs. Community-based health insurance (CBHI) schemes have multiplied since the 1990s in West Africa. They have significantly improved their members’ access to health care. However, a large proportion of users are reluctant to subscribe to a local CBHI. Identifying the major factors affecting membership will be useful for improving CBHI coverage. The objective of this research is to obtain a general overview of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…No study was excluded from the reviews using the above appraisal tools. The following criteria were utilized to evaluate cross-sectional studies: (1) adherence to inclusion criteria, (2) clear description of study subjects and settings, (3) utilization of valid and reliable exposure measurements, (4) utilization of objective and standardized criteria, (5) identification of confounding factors, (6) implementation of strategies to address confounding, (7) appropriate outcome measurement, and (8) utilization of suitable statistical analysis (Table 2).…”
Section: Results Of Study Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…No study was excluded from the reviews using the above appraisal tools. The following criteria were utilized to evaluate cross-sectional studies: (1) adherence to inclusion criteria, (2) clear description of study subjects and settings, (3) utilization of valid and reliable exposure measurements, (4) utilization of objective and standardized criteria, (5) identification of confounding factors, (6) implementation of strategies to address confounding, (7) appropriate outcome measurement, and (8) utilization of suitable statistical analysis (Table 2).…”
Section: Results Of Study Bias Assessmentmentioning
confidence: 99%
“…Evidence showed that various sociodemographic characteristics, including age, educational status, income, and distance to healthcare facilities, influence enrolment in CBHI schemes. Additionally, factors related to the health facilities, such as the quality of care provided, trust in administrators, and access to information about CBHI, also play crucial roles in determining CBHI membership [7,8]. Another challenge LMICs face in the context of CBHI schemes is a high dropout rate among enrolled members [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, factors related to the health facilities, such as the access to information about CBHI, also play crucial roles in determining CBHI membership [ 26 ]. The current study revealed that being informed about the scheme was significantly associated with the willingness to join for community-based health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…In their search for solutions to cover their citizens with health insurance, African countries face many challenges and have tested various strategies (1). In Francophone West Africa, community-based health insurance (CBHI) has long been the preferred instrument for covering populations in the informal and rural sectors (2)(3)(4). However, while evidence shows CBHIs protect their members (3,5), their penetration rates are very low.…”
Section: Introductionmentioning
confidence: 99%
“…In Francophone West Africa, community-based health insurance (CBHI) has long been the preferred instrument for covering populations in the informal and rural sectors (2)(3)(4). However, while evidence shows CBHIs protect their members (3,5), their penetration rates are very low. In Senegal, less than 5 % of the population is affiliated with a CBHI (6,7) despite membership being subsidized and the fact that they have been at the heart of the health financing policy for over a decade (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%